Corpus Linguistics in Discourse Analysis: Toward Inclusive and Critical Frameworks - Wiyanti, Endang; Bahari, Septiyan Darma; Ayuningtyas, Diah Ikawati; Wahyuddin, Nur rahmah (Lingua : Journal of Linguistics and Language, 2025)
This study provides a comprehensive narrative review of the integration of corpus linguistics and discourse analysis, examining how methodological and contextual factors influence the field. The objective is to assess the role of corpus methodologies in enhancing discourse analysis while identifying key challenges and future directions. A systematic search of major databases including Scopus, PubMed, and Google Scholar was conducted using targeted keywords related to corpus linguistics and discourse analysis. Inclusion criteria prioritized peer-reviewed empirical and theoretical studies published in the last decade, while irrelevant and non-scholarly works were excluded. The analysis identified four major themes: technological integration, pedagogical applications, policy and institutional contexts, and socio-cultural influences. Results show that technological tools have greatly improved linguistic analysis, though regional disparities in access persist. Pedagogical applications demonstrate improved student outcomes, yet adoption varies across educational cultures. Policy frameworks were shown to shape discourse in areas such as migration and public health, while socio-cultural factors were found to be critical in constructing identities and narratives. The discussion highlights systemic barriers including funding inequalities and political restrictions, as well as opportunities for methodological innovation through integrated frameworks and collaborative research. The review concludes that advancing corpus linguistics in discourse analysis requires both methodological pluralism and systemic reform, with implications for education, policy, and global discourse studies.